Spinning solution based on acrylonitrile terpolymer and preparation method thereof
By using terpolymer spinning solutions, combined with antioxidants and rheology modifiers, the problems of insufficient thermal stability and viscosity of existing spinning solutions have been solved, enabling efficient and low-cost carbon fiber production to meet the needs of high-end applications.
Patent Information
- Application Number
- CN202511582119.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-31
- Publication Date
- 2026-01-23
AI Technical Summary
Existing acrylonitrile copolymer spinning solutions suffer from poor thermal stability and insufficient viscosity stability, resulting in low preparation efficiency and making it difficult to meet the industrial production needs of high-end carbon fibers.
A terpolymer spinning solution is used, which includes acrylonitrile, maleimide group compounds and bisphenol A ethoxy acid diacrylate as the main monomers. Antioxidants and rheology modifiers are added, and the polymerization reaction parameters are optimized to form a spinning solution with high thermal stability and high viscosity stability.
It improves the thermal and viscosity stability of the spinning solution, shortens the preparation cycle, reduces production costs, and is suitable for large-scale industrial production. The prepared carbon fiber precursor has excellent mechanical properties.
Smart Images

Figure CN121381206A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of high polymers, and particularly relates to a spinning dope based on acrylonitrile terpolymer and a preparation method thereof. BACKGROUND
[0002] Polyacrylonitrile-based carbon fibers have excellent properties such as high strength, high modulus, corrosion resistance and fatigue resistance, and are indispensable strategic materials for China's economic development and national defense construction, and are widely used in aerospace and wind power and other fields. According to the different mechanical properties, carbon fibers can be divided into high-strength and high-modulus, high-strength and medium-modulus, high-modulus and high-strength, etc. Fiber diameter is one of the key parameters affecting its strength and modulus. In order to obtain higher strength carbon fibers, the diameter is usually reduced to improve the uniformity of the radial structure. However, reducing the diameter will cause problems such as imbalance of the tensile-compressive ratio of the composite material. Therefore, under the premise of maintaining the existing performance of high-strength and medium-modulus carbon fibers, increasing the fiber diameter is of great significance to improve production efficiency, reduce production cost and improve the compression performance of the composite material.
[0003] At present, the acrylonitrile copolymer commonly used in industry is mostly binary copolymer, such as acrylonitrile-itaconic acid and acrylonitrile-methyl acrylate system. However, the binary copolymer spinning dope has the following limitations: first, the thermal stability is insufficient, and excessive crosslinking or thermal cracking is easy to occur in the subsequent pre-oxidation process, resulting in defects in the precursor fiber; second, the viscosity stability of the spinning dope is poor, and gel or stratification is easy to occur during storage, affecting the continuity of spinning; third, the compatibility with the coagulation bath is poor, and the skin-core structure is easy to occur during spinning, reducing the mechanical uniformity of the fiber. In order to improve the above problems, researchers try to introduce a third monomer to prepare a ternary copolymer.
[0004] Chinese patent CN119081000A discloses a kind of acrylonitrile-maleic anhydride-itaconic acid ternary copolymer spinning dope, although the pre-oxidation exothermic peak temperature is reduced, but the exothermic peak is still relatively concentrated, and the exothermic interval is still relatively large, and the shear viscosity of the dope fluctuates greatly with the change of shear rate, and the spinning process is easy to occur broken filament phenomenon, and the industrial adaptability is poor.
[0005] Chinese patent CN119221149A discloses a kind of acrylonitrile-3-carboxylic acid ammonium-3-butyl acid methyl ester-methyl acrylate ternary copolymer spinning dope, which improves the thermal stability and reduces the skin-core structure. Although the thermal performance is improved, the reaction time is long, the temperature rising process is complex, and two exothermic peaks appear in the DSC curve, indicating that the heat transfer is uneven, and phase separation or microstructure is produced, which is not conducive to the subsequent pre-oxidation.
[0006] In addition, the preparation of the existing spinning dope is mostly by the traditional solution polymerization method, which has the problems of long reaction time (usually 8-12 hours), low monomer conversion rate, and great difficulty in solvent recovery, resulting in high production cost and difficulty in realizing large-scale continuous production. Therefore, it is an urgent need to develop a kind of acrylonitrile terpolymer spinning dope with high thermal stability, high viscosity stability and efficient preparation process, so as to promote the development of polyacrylonitrile-based carbon fiber to high-end and low-cost. SUMMARY
[0007] In view of the defects of the prior art, the technical problem to be solved by the present application is to provide a spinning dope based on acrylonitrile terpolymer and a preparation method thereof, which overcomes the defects of poor thermal stability, insufficient viscosity stability and low preparation efficiency of the existing acrylonitrile copolymer spinning dope, and provides a kind of acrylonitrile terpolymer spinning dope with high thermal stability and a preparation method thereof, which improves the thermal stability, rheological properties and molding effect of the spinning dope, shortens the preparation cycle, reduces the production cost, and meets the industrial production needs of high-end carbon fiber precursors.
[0008] The present application provides a kind of spinning dope, the spinning dope component includes terpolymer, antioxidant and rheological modifier;Wherein the terpolymer is with the raw material of first monomer acrylonitrile, second monomer containing maleimide group compound, third monomer bisphenol A ethoxy acid dipropylene acid, is obtained by polymerization reaction.
[0009] The molecular weight of the polymer in the spinning dope is 100-200 thousand, and the molecular weight distribution is less than 2.5;The viscosity of the acrylonitrile terpolymer spinning dope at 40℃ is 600-1000P.
[0010] The present application provides a kind of preparation method of spinning dope, comprising:
[0011] (1) the first monomer, the second monomer, the third monomer, the solvent are mixed, and the polymer stock solution is obtained under the condition of initiator and inert atmosphere;Wherein the first monomer is acrylonitrile;The second monomer contains maleimide group compound;The third monomer is bisphenol A ethoxy acid dipropylene acid;
[0012] (2) the polymer stock solution, antioxidant, rheological modifier are mixed, and the spinning dope is obtained.
[0013] Preferably, the step (1) contains maleimide group compound
[0014] , wherein the R group includes one or more of carboxyl, carboxyl group, maleimide group and benzene ring.
[0015] Further preferably, the maleimide group-containing compound includes one or more of maleimide propionic acid, N-phenyl maleimide, diphenylmethane bismaleimide, 6- (maleimide) hexanoic acid succinimidyl ester.
[0016] The structure of the third monomer bisphenol A ethoxy acid diacrylate is:
[0017] .
[0018] Preferably, the solvent in step (1) includes one or more of dimethyl sulfoxide, dimethyl acetamide, aqueous sodium thiocyanate; the initiator includes one or more of azobisisobutyronitrile, benzoyl peroxide.
[0019] Preferably, the sum of the mass of the second monomer and the third monomer in step (1) is 0.5-15wt% of the mass of the acrylonitrile; the mass of the third monomer is 20-50wt% of the mass of the second monomer; the sum of the mass of the acrylonitrile, the second monomer and the third monomer is 10-40wt% of the mass of the solvent.
[0020] Further, the mass ratio of the acrylonitrile, the second monomer and the third monomer is 85-100: 0.25-10: 0.1-7.5.
[0021] Preferably, the initiator in step (1) is 0.1-1wt% of the total mass of the monomers (the sum of the first, second and third monomers).
[0022] Preferably, the inert atmosphere in step (1) includes at least one of a nitrogen atmosphere, an argon atmosphere, a helium atmosphere.
[0023] Preferably, the reaction temperature is 60-90℃, the time is 1-6h; the polymerization reaction pressure is 0.05-1MPa.
[0024] In step (1), the first monomer, the second monomer, the third monomer and the solvent are mixed and introduced into an inert atmosphere to exclude air, and under the protection of the inert atmosphere, the temperature is raised to 60-90℃, the initiator is added, and the constant temperature reaction is carried out under a pressure of 0.05-1MPa for 1-6h to obtain a polymer stock solution.
[0025] Preferably, the mass ratio of the antioxidant and the rheology modifier in step (2) is 1: 1-2: 1.
[0026] Preferably, the antioxidant in step (2) includes one or more of hindered phenolic antioxidants; the rheology modifier includes one or more of polyethylene glycol, polypropylene glycol, tributyl phosphate.
[0027] Preferably, the step (2) wherein the total mass of the antioxidant and rheology modifier is controlled at 0.5% to 2% of the total mass of the monomer.
[0028] Further, the hindered phenol antioxidant includes one or more of antioxidant 1010, antioxidant 1098, and antioxidant 1076; and the polyethylene glycol includes polyethylene glycol 400.
[0029] The present application provides a fiber material, which is obtained by using a spinning dope as a raw material.
[0030] The fiber material is prepared by using a spinning dope as a raw material and by spinning.
[0031] The preparation of the fiber material includes: after the spinning dope is solidified and formed by a coagulation bath, one or more of the following processes is selected: drawing, water washing, oiling, drying and densification, steam drawing, and drying, to obtain a polyacrylonitrile carbon fiber precursor, which has excellent mechanical properties and good thermal stability. The polyacrylonitrile carbon fiber precursor can be further processed into a polyacrylonitrile-based carbon fiber.
[0032] Preferably, the coagulation bath uses water as a non-solvent, and is combined with dimethyl sulfoxide (DMSO) at a concentration of 30-50 wt%, and is kept at 5-10℃ for 2-4s.
[0033] Preferably, the drawing ratio is 2.0-5.0 during the spinning process.
[0034] Preferably, the water washing process is performed at a temperature of 40-80℃.
[0035] Preferably, the heat drawing process is performed at a temperature of 75-100℃, and the drawing ratio is 2.0-5.0.
[0036] Preferably, in the oiling process, the oil agent is an organic silicon oil agent, and the oiling rate is 1.0-1.5%.
[0037] Preferably, the drying and densification process is performed at a temperature of 95-125℃.
[0038] Preferably, in the steam drawing process, the drawing ratio is 2.5-6.0, preferably 5.0-6.0.
[0039] Preferably, the drying process is performed at a temperature of 100-120℃.
[0040] The present application provides an application of the fiber material in the fields of aerospace, wind power generation, rail transportation, and pressure vessels.
[0041] Compared with the existing binary copolymer spinning dope and traditional preparation process, the product of the application has significantly improved thermal stability, can avoid excessive crosslinking or thermal cracking in the pre-oxidation process, has enhanced viscosity stability, reduces gel or stratification phenomenon during storage, shortens the preparation cycle, far lower reaction time than the traditional 8-12h, increases monomer conversion rate, reduces solvent recovery difficulty and production cost, is suitable for large-scale industrial production of high-end polyacrylonitrile-based carbon fiber precursor, and has important significance for promoting the development of carbon fiber to high-end and low-cost.
[0042] Advantages
[0043] (1) The application selects the second monomer (containing maleimide group substance) and the third monomer (bisphenol A ethoxy acid dipropylene acid) reasonably, and optimizes the ratio of the three, the maleimide group contained in the second monomer can enhance the stability of the copolymer main chain through the rigid ring structure in the molecular structure. Its core function comes from the maleimide rigid ring in its molecular structure: on the one hand, the six-membered ring structure can enhance the spatial rigidity of the copolymer main chain, weaken the strong hydrogen bond interaction between acrylonitrile molecules, and avoid the formation of gel or stratification due to molecular aggregation during the storage of the spinning dope; on the other hand, during the pre-oxidation process, the maleimide ring can slowly release active hydrogen, regulate the cyclization reaction rate of the acrylonitrile unit, narrow the exothermic peak temperature interval, and prevent the fiber from being brittle due to excessive crosslinking. In addition, different R groups (carboxyl, benzene ring) can further fine-tune the reactivity of the monomer: the R group containing carboxyl (such as 3-maleimide propionic acid) can improve the compatibility of the monomer with the solvent, and the R group containing benzene ring (such as N-phenyl maleimide) can further enhance the thermal stability of the copolymer, effectively weaken the strong interaction between acrylonitrile molecules, and avoid the gel or stratification due to molecular aggregation during the storage of the spinning dope;
[0044] (2) The application introduces the third monomer bisphenol A ethoxy acid dipropylene acid, the double acrylate groups in its molecular structure can form a more uniform copolymer network with acrylonitrile and the second monomer, on the one hand, it can improve the rheological properties of the spinning dope, increase the viscosity stability at 40℃, and reduce the yarn breakage caused by viscosity fluctuation during spinning; on the other hand, the structural design of the third monomer realizes 'rigidity-flexibility-reactivity' synergy: first, the rigid backbone of bisphenol A can form 'double rigid support' with the maleimide ring of the second monomer, so that the thermal decomposition temperature of the copolymer is increased, and there is no obvious thermal cracking during the pre-oxidation stage; second, the flexible segment of ethoxy acid can reduce the shear viscosity sensitivity of the spinning dope, and reduce the yarn breakage rate; third, the acrylate double bond groups at both ends can copolymerize with the double bonds of acrylonitrile and the second monomer, forming a three-dimensional crosslinked network, optimizing the interface action between the spinning dope and the coagulation bath, and making the fiber skin-core structure thickness ratio lower than that of the traditional binary system, and improving the radial structure uniformity of the fiber.
[0045] (3) The application adds specific proportion of antioxidant and rheological modifier in the preparation process, significantly improves the viscosity stability of the spinning dope, and reduces the gelation or stratification phenomenon during storage, ensures the continuity of spinning, reduces the yarn breakage rate during spinning, and improves the industrial adaptability.
[0046] (4) The application optimizes the polymerization reaction process parameters, shortens the reaction time (only 1-6h, compared with the traditional process of 8-12h, which is greatly shortened), improves the monomer conversion rate (more than 90%), reduces the solvent production cost, and is suitable for large-scale industrial continuous production.
[0047] (5) The high-performance acrylonitrile terpolymer spinning dope prepared by the application can be used to prepare polyacrylonitrile carbon fiber precursor with excellent mechanical properties, and the polymer molecular weight is controllable (100-200 thousand), and the molecular weight distribution is narrow (less than 2.5), which lays a good foundation for the subsequent preparation of high-strength and high-modulus polyacrylonitrile-based carbon fiber, and expands its application prospect in high-end fields such as aerospace and wind power. BRIEF DESCRIPTION OF DRAWINGS
[0048] Figure 1 DSC chart in Example 1. DETAILED DESCRIPTION
[0049] The application will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the application and not to limit the scope of the application. In addition, it should be understood that after reading the content taught by the application, those skilled in the art can make various modifications or modifications to the application, and these equivalent forms also fall within the scope defined by the claims attached to the present application.
[0050] Among them, the XQ-1 type monofilament strength tester is used, and the mechanical properties such as single filament breaking strength and elongation at break of the fiber sample are tested according to GB / T31290-2022.
[0051] The 209-F1 type differential scanning calorimeter of Germany's Nanjing Company is used, and the sample is tested under nitrogen atmosphere according to GB / T19466.3-2004.
[0052] The rotational viscometer method (according to GB / T10247-2008 "Viscosity measurement method") is used to test the viscosity of the sample.
[0053] The GPC50 type gel chromatograph of American Polymer Laboratories Company is used to test the sample, and hexafluoroisopropanol is used as the solvent and mobile phase to test the sample.
[0054] The spinning dope storage stability test conditions are temperature 25℃ and relative humidity 50%.
[0055] The spinning dope in the examples and comparative examples is coagulated into a shape by a coagulation bath, and after drawing, water washing, oiling, drying and densification, steam drawing and drying and heat setting, polyacrylonitrile carbon fiber precursor is prepared.
[0056] The spinning dope filament is sprayed into a coagulation bath with a temperature of 10℃, and the content of dimethyl sulfoxide in the coagulation bath is 40%; the obtained coagulation filament is guided by a guide roller and subjected to segmented drawing in a mixture of dimethyl sulfoxide and water with a dimethyl sulfoxide content of 2-10% and a temperature of 80-99℃, and the total drawing ratio is 5; the filament is subjected to multi-stage water washing, and the water washing temperature is 60℃. The water-washed filament is subjected to oiling, drying and densification at a temperature of 100-125℃, and then is drawn by 3 times under saturated water vapor with a pressure of 0.1 MPa, and is dried at 120℃ to obtain high-performance polyacrylonitrile-based carbon fiber.
[0057] Example 1
[0058] (1) A first monomer acrylonitrile 100 g, a second monomer 3-maleimido propionic acid 2 g, and a third monomer bisphenol A ethoxy acid dipropenoic acid 0.4 g (the mass of the third monomer is 20 wt% of the mass of the second monomer) are weighed according to the proportion, and are dissolved in 450 g of an aqueous sodium thiocyanate solution (the total mass of the monomers is 22.7 wt% of the mass of the solvent) to obtain a mixed monomer solution;
[0059] (2) The mixed monomer solution is placed in a four-necked flask, stirring is started, and nitrogen is introduced to remove air. Under nitrogen protection, the temperature is raised to 60℃, an initiator azobisisobutyronitrile 0.1024 g (the mass of the initiator is 0.1 wt% of the total mass of the monomers) is added, and the reaction is carried out at a pressure of 0.05 MPa for 1 h to obtain a polymer dope;
[0060] (3) After the reaction is completed, the polymer dope is cooled to room temperature, an antioxidant hindered phenol (1010) 0.5 g and a rheological modifier polyethylene glycol (400) 0.5 g (mass ratio 1:1) are added, and stirring is continued for 30 min until they are uniformly mixed to obtain a high-performance acrylonitrile terpolymer spinning dope;
[0061] The properties of the spinning dope are detected, and the polymer has a molecular weight of 120,000, a molecular weight distribution of 2.2, and a viscosity of 650 P at 40℃. The spinning dope is subjected to dry-jet wet spinning, drawing, oiling, drying and densification, heat steam drawing, and heat setting to prepare a polyacrylonitrile carbon fiber precursor, and the tensile strength of the precursor is 6.2 GPa, and the pre-oxidation exothermic peak temperature interval in the thermal stability test is narrow and flat.
[0062] As Figure 1As shown, the termonomer described in Example 1 starts to release heat at 214.3°C, reaches the peak of heat release at 263.4°C, and ends at 307.2°C, which is lower than the peak of heat release of conventional acrylonitrile itaconic acid copolymer, the heat release rate is reduced, and the heat release interval is increased, and the polymer thermal stability is improved compared with the conventional acrylonitrile precursor.
[0063] Example 2
[0064] (1) Take acrylonitrile 100 g, second monomer N-phenyl maleimide 5 g, third monomer bisphenol A ethoxy acid dipropylene acid 2.5 g (the mass of the third monomer is 50 wt% of the mass of the second monomer), and dissolve in 350 g of dimethyl sulfoxide (the total mass of the monomers is 30 wt% of the mass of the solvent), stir and dissolve to obtain a mixed monomer solution;
[0065] (2) Put the mixed monomer solution into a four-necked flask, purge the air with argon, heat to 75°C, add benzoyl peroxide 0.5375 g (the mass of the initiator is 0.5 wt% of the total mass of the monomers), and react at a constant temperature of 0.5 MPa for 3 h to obtain a polymer stock solution;
[0066] (3) After cooling, add hindered phenol (antioxidant 1010) 0.8 g and polyethylene glycol 0.4 g (mass ratio 2:1), stir uniformly to obtain a spinning stock solution;
[0067] Detect the spinning stock solution, the polymer molecular weight is 150,000, the molecular weight distribution is 2.0, and the viscosity at 40°C is 800P;
[0068] The prepared polyacrylonitrile carbon fiber precursor has a tensile strength of 6.8 GPa and excellent thermal stability, and no obvious overcrosslinking phenomenon occurs during the pre-oxidation process.
[0069] Example 3
[0070] (1) Take acrylonitrile 100 g, second monomer diphenyl methane bismaleimide 10 g, third monomer bisphenol A ethoxy acid dipropylene acid 3 g (the mass of the third monomer is 30 wt% of the mass of the second monomer), and dissolve in 785.7 g of dimethyl acetamide (the total mass of the monomers is 14 wt% of the mass of the solvent), stir and dissolve to obtain a mixed monomer solution;
[0071] (2) Put the mixed monomer solution into a four-necked flask, purge the air with nitrogen, heat to 90°C, add azobisisobutyronitrile 1.13 g (the mass of the initiator is 1 wt% of the total mass of the monomers), and react at a constant temperature of 1 MPa for 1 h to obtain a polymer stock solution;
[0072] (3) After cooling, add hindered phenol (antioxidant 1010) 1 g and polyethylene glycol 0.5 g (mass ratio 2:1), stir uniformly to obtain a spinning stock solution;
[0073] The polymer solution has a polymer molecular weight of 200,000, a molecular weight distribution of 2.4, and a viscosity of 1000 P at 40°C.
[0074] The prepared polyacrylonitrile carbon fiber precursor has a tensile strength of 7.2 GPa and good thermal stability, and no broken filament phenomenon occurs in the spinning process.
[0075] Example 4
[0076] (1) Take acrylonitrile 100 g, second monomer 6-(maleimide) hexanoic acid succinimidyl ester 0.5 g, and third monomer bisphenol A ethoxy acid dipropenoic acid 0.1 g (the mass of the third monomer is 20 wt% of the mass of the second monomer), dissolve in 2010 g of sodium thiocyanate aqueous solution (the total mass of the monomers is 10 wt% of the mass of the solvent), stir and dissolve to obtain a mixed monomer solution;
[0077] (2) Put the mixed monomer solution into a four-necked flask, purge air with helium, heat to 65°C, add 0.2012 g of azobisisobutyronitrile (the mass of the initiator is 0.2 wt% of the total mass of the monomers), and react at a constant temperature of 0.2 MPa for 4 h to obtain a polymer solution;
[0078] (3) After cooling, add 0.3 g of hindered phenol (antioxidant 1010) and 0.3 g of polyethylene glycol (mass ratio 1:1) and stir uniformly to obtain a spinning solution;
[0079] The polymer solution has a polymer molecular weight of 200,000, a molecular weight distribution of 2.4, and a viscosity of 1000 P at 40°C.
[0080] The prepared polyacrylonitrile carbon fiber precursor has a tensile strength of 7.2 GPa and good thermal stability, and no broken filament phenomenon occurs in the spinning process.
[0081] Example 5
[0082] (1) Take acrylonitrile 100 g, second monomer 3-maleimide propionic acid 8 g, and third monomer bisphenol A ethoxy acid dipropenoic acid 3.2 g (the mass of the third monomer is 40 wt% of the mass of the second monomer), dissolve in 322.9 g of sodium thiocyanate aqueous solution (the total mass of the monomers is 34.4 wt% of the mass of the solvent), stir and dissolve to obtain a mixed monomer solution;
[0083] (2) Put the mixed monomer solution into a four-necked flask, purge air with nitrogen, heat to 80°C, add 0.8448 g of azobisisobutyronitrile (the mass of the initiator is 0.8 wt% of the total mass of the monomers), and react at a constant temperature of 0.8 MPa for 2 h to obtain a polymer solution;
[0084] (3) After cooling, 0.6 g of hindered phenol (antioxidant 1010) and 0.4 g of polyethylene glycol (mass ratio 3:2) were added and stirred uniformly to obtain a spinning dope;
[0085] The spinning dope was detected, and the polymer molecular weight was 180,000, the molecular weight distribution was 2.3, and the viscosity at 40°C was 900P;
[0086] The prepared polyacrylonitrile carbon fiber precursor had a tensile strength of 7.0 GPa and excellent thermal stability, and the monomer conversion rate reached 92%.
[0087] Comparative Example 1
[0088] This comparative example was basically the same as Example 1, except that the third monomer bisphenol A ethoxy acid dipropylene acid was not added, and only an acrylonitrile-3-maleimide propionic acid binary copolymer system was used.
[0089] The detection results showed that the prepared spinning dope had a viscosity of 500P at 40°C, and slight gelation occurred after 48h of storage; the prepared polyacrylonitrile carbon fiber precursor had a tensile strength of 4.5 GPa, and the thermal performance decreased, the exothermic interval decreased, and the concentrated exothermic was obvious.
[0090] Comparative Example 2
[0091] This comparative example was basically the same as Example 1, except that no antioxidant and rheological modifier was added.
[0092] The detection results showed that the spinning dope had a viscosity of 620P at 40°C, but obvious stratification occurred after 36h of storage; the yarn breakage rate was high during the spinning process, and the prepared polyacrylonitrile carbon fiber precursor had a tensile strength of 5.0 GPa, and the exothermic peak was relatively concentrated in the thermal stability test.
[0093] Comparative Example 3
[0094] This comparative example was basically the same as Example 1, except that the polymerization reaction temperature was 50°C and the reaction time was 10h (exceeding the process parameter range set by the application).
[0095] The detection results showed that the monomer conversion rate was only 75%, the polymer molecular weight was 80,000, and the molecular weight distribution was 3.0; the spinning dope had a viscosity of 450P at 40°C, and the prepared polyacrylonitrile carbon fiber precursor had a tensile strength of 4.2 GPa, which could not meet the requirements of high-end applications.
[0096] Comparative Example 4
[0097] This comparative example was basically the same as Example 1, except that the mass ratio of antioxidant to rheological modifier was 3:1 (exceeding the range of 1:1-2:1 set by the application).
[0098] The detection result shows that the spinning dope has a viscosity of 700 P at 40 DEG C, but burrs appear on the fiber surface during the spinning process; and the tensile strength of the polyacrylonitrile carbon fiber precursor prepared is 5.2 GPa, and the mechanical uniformity is poor.
[0099] Table 1
[0100]
[0101] As shown in the data in Table 1, the high-performance acrylonitrile terpolymer spinning dope prepared in Examples 1-5 and the polyacrylonitrile carbon fiber precursor prepared therefrom are significantly superior to Comparative Examples 2-4 in terms of the spinning dope viscosity stability, storage stability, polymer molecular weight and distribution, and the precursor tensile strength and pre-oxidation exothermic peak.
[0102] Comparative Example 1 has a reduced precursor strength and serious gelation due to the lack of synergistic effect of the third monomer in the binary copolymerization system; Comparative Example 2 has poor spinning dope storage stability due to the lack of additives, and the precursor strength and thermal stability are affected; Comparative Example 3 has a low monomer conversion rate, a small polymer molecular weight and a wide distribution, and a poor precursor performance due to the polymerization process parameters beyond the range of the present application; and Comparative Example 4 has a decreased precursor mechanical uniformity and strength due to the additive ratio beyond the range.
[0103] As shown by the data of Comparative Examples 1-5, within the process parameter range set by the present application, the monomer ratio, polymerization temperature, reaction time and additive ratio can be adjusted to prepare spinning dopes with different performances to meet the needs of different application scenarios, but the products of all examples meet the requirements of high thermal stability, high viscosity stability and high mechanical properties, fully proving the effectiveness and superiority of the technical solution of the present application.
Claims
1. A dope, characterized by, The spinning dope component comprises a terpolymer, an antioxidant and a rheological modifier; wherein the terpolymer is obtained by polymerization reaction with raw materials comprising a first monomer acrylonitrile, a second monomer maleimide group-containing compound and a third monomer bisphenol A ethoxy acid dipropenoic acid.
2. A preparation method of a spinning dope, comprising: (1) mixing a first monomer, a second monomer, a third monomer and a solvent, and reacting under the condition of an initiator and an inert atmosphere to obtain a polymer dope; wherein the first monomer is acrylonitrile; the second monomer is a maleimide group-containing compound; and the third monomer is bisphenol A ethoxy acid dipropenoic acid; (2) mixing the polymer dope, an antioxidant and a rheological modifier to obtain the spinning dope.
3. The preparation method according to claim 2, characterized in that, The maleimide group-containing compound in step (1) is one or more of maleimide propionic acid, N-phenyl maleimide, diphenyl methane bismaleimide and 6- (maleimide) hexanoic acid succinimidyl ester. wherein the R groups include one or more of carboxyl, carboxylate, maleimido, benzene rings.
4. The preparation method according to claim 3, characterized in that, The solvent in step (1) comprises one or more of dimethyl sulfoxide, dimethyl acetamide and aqueous sodium thiocyanate; and the initiator comprises one or more of azobisisobutyronitrile and benzoyl peroxide.
5. The preparation method according to claim 2, characterized in that, The sum of the mass of the second monomer and the third monomer in step (1) is 0.5-15wt% of the mass of acrylonitrile; the mass of the third monomer is 20-50wt% of the mass of the second monomer; and the sum of the mass of acrylonitrile, the second monomer and the third monomer is 10-40wt% of the mass of the solvent.
6. The preparation method according to claim 2, characterized in that, The initiator in step (1) is 0.1-1wt% of the total mass of monomers. The inert atmosphere in step (1) comprises at least one of nitrogen atmosphere, argon atmosphere and helium atmosphere.
7. The preparation method according to claim 2, characterized in that, The reaction temperature is 60-90℃, the reaction time is 1-6h, and the polymerization reaction pressure is 0.05-1MPa. The mass ratio of the antioxidant to the rheological modifier in step (2) is 1:1-2:
1.
8. The preparation method according to claim 2, characterized in that, The antioxidant in step (2) comprises one or more hindered phenolic antioxidants; and the rheological modifier comprises one or more of polyethylene glycol, polypropylene glycol and tributyl phosphate. The fiber material is obtained with the spinning dope of claim 1 as raw material.
9. A fibrous material, characterized by 10. Application of the fiber material of claim 9 in the fields of aerospace, wind power generation, rail transit and pressure vessels.
Citation Information
Patent Citations
Preparation method of acrylonitrile-maleic anhydride-itaconic acid terpolymer
CN119081000A
Acrylonitrile terpolymer high-strength spinning solution and preparation method thereof
CN119221149A
